Impact of sintering temperature on structural, optical and ferroelectric properties of V-doped ZnO. (14th April 2015) - Kumar, Parmod; Joshi, Rahul; Gaur, Anurag; Kumar, Lalit; Asokan, K
Abstract: This paper reports the effect of sintering temperature on the structural, optical and ferroelectric properties of vanadium (V) doped zinc oxide (ZnO) samples. X-ray diffraction (XRD) study confirms the formation of a hexagonal wurtzite phase. It has been found that the increase in sintering temperature leads to very small enhancement in lattice parameters as well as in grain sizes. The presence of E2 (high) modes in Raman spectra of V-doped ZnO indicate the stability of the wurtzite structure of ZnO, consistent with the XRD results. The optical band gap estimated from UV–Vis spectroscopy reveals the reduction in band gap of ZnO. Furthermore, changes in ferroelectric polarizations are also observed with an increase in the sintering temperature. The above results are understood based on the increased crystallinity and the presence of mixed phases of the samples with sintering temperature.